Risk for Cervical Intraepithelial Neoplasia in Systemic Lupus Erythematosus is not Related to Disease Severity - P. Dhar, Josephine; Gregoire, Lucie; Lancaster, Wayne; Stark, Azadah; G. Schwartz, Ann; Schultz, Daniel; Essenmacher, Lynnette; Ager, Joel; Chiodo, Lisa; Husain, Mujitaba; J. Sokol, Robert (Current Rheumatology Reviews, 2013)
Introduction: Cervical intraepithelial neoplasia (CIN) is increased in women with systemic lupus erythematosus (SLE). Cervical neoplasia is caused by human papilloma virus (HPV) infection which persists and causes malignant transformation of infected cervical cells. Women with lupus have impaired immune systems which can facilitate HPV persistence. We hypothesized that women with SLE who developed CIN would be younger, have more severe disease and received more immunosuppressive treatment. To test this hypothesis, a case-control study was conducted focusing on two key variables, SLE disease severity and immunosuppressive treatment, which we believed would be the major determinants of CIN development in SLE. Methods: A case control analysis was performed to compare the clinical characteristics of SLE women with cervical neoplasia (cases) to SLE women without cervical neoplasia (controls). Formalin fixed blocks of neoplastic cervical tissue were obtained from 113 women with SLE and tissue histology confirmed by 2 pathologists. Clinical data was obtained by retrospective chart reviews. Logistic regression was used to evaluate for any significant differences in clinical variables between the cases and the controls. Two sets of controls were used for comparison with a 2:1 match for each control group to cases group. Results: Using matched controls adjusting for age and race, logistic regression analysis showed no significant difference between cases and controls for any of the clinical variables. In particular, there were no significant differences between cases vs. matched and vs. unmatched controls for factors related to SLE (disease severity, use of immunosuppressive drugs), chronic metabolic diseases (hypertension, diabetes) and HPV risk factors (marital status, smoking, gravidity parity). Conclusion: The key finding of this study is that SLE patients who develop CIN are not clinically different from SLE patients who do not develop CIN. Thus, lupus disease severity and immunosuppressive treatment were not susceptibility factors for CIN in our female lupus cohort.
Keywords: neoplasia